Novel Projections to the Cerebrospinal Fluid-Contacting Nucleus From the Subcortex and Limbic System in Rat - Si-Yuan Song; Xiao-Meng Zhai; Jia-Hao Dai; Lei-Lei Lu; Cheng-Jing Shan; Jia Hong; Jun-Li Cao; Li-Cai Zhang (Frontiers Media S.A., 2020)
Objective: To identify the novel projections received by the cerebrospinal fluid (CSF)-contacting nucleus from the subcortex and limbic system to understand the biological functions of the nucleus.Methods: The cholera toxin subunit B (CB), a retrograde tracer, was injected into the CSF-contacting nucleus in Sprague-Dawley rats. After 7-10 days, the surviving rats were perfused, and the whole brain and spinal cord were sliced for CB immunofluorescence detection. The CB-positive neurons in the subcortex and limbic system were observed under a fluorescence microscope, followed by 3D reconstructed with the imaris software.Results: CB-positive neurons were found in the basal forebrain, septum, periventricular organs, preoptic area, and amygdaloid structures. Five functional areas including 46 sub-regions sent projections to the CSF-contacting nucleus. However, the projections had different densities, ranging from sparse to moderate, to dense.Conclusions: According to the projections from the subcortex and limbic system, we hypothesize that the CSF-contacting nucleus participates in emotion, cognition, homeostasis regulation, visceral activity, pain, and addiction. In this study, we illustrate the novel projections from the subcortex and limbic system to the CSF-contacting nucleus, which underlies the diverse and complicated circuits of the nucleus in body regulations.